Hemogasometry, cardiac biomarkers and blood metabolites in goats with experimentally induced acute ruminal lactic acidosis - Ribeiro, Ana Clara Sarzedas; da Conceição, Ângela Imperiano; Soares, Gliére Silmara Leite; Correia, Felipe Rosendo; de Oliveira-Filho, José Paes [UNESP]; Soares, Pierre Castro; de Mendonça, Carla Lopes; Afonso, José Augusto Bastos (Elsevier, 2020)
Whereas that acute ruminal lactic acidosis (ARLA) can cause secondary metabolic disorders and some degree of cardiovascular damage, the present study aimed to evaluate the hemogasometry, concentrations of the creatine kinase isoenzyme MB (CKMB), cardiac troponin I (cTnI), and blood variables in goats with experimental ARLA. The disease was induced in five goats through intraruminal supply of 15 g sucrose/Kg live weight. Before induction and 4 h, 8 h, 12 h, 24 h, 48 h, 72 h, and 168 h post-induction (PI), clinical examination, ruminal fluid analysis, hemogasometry analysis, and measurement of AST, CK, CK-MB, cTnI, GGT, LDH, and L-lactate in the blood of these animals were performed. The experimental model used caused clinical alterations characteristic of ARLA in goats from 4 h PI. The characteristics of the ruminal fluid also changed from 4 h PI, becoming to milky appearance, acidic odor, aqueous consistency and a reduced population of protozoa. The ruminal pH decreased (P <.0001) from 4 h to 48 h PI, with a lower average value of 4.70–12 h PI. Hemogasometry revealed that acid-base and electrolyte imbalances occurred, with transient metabolic alkalosis preceding a metabolic acidosis. The blood concentration of Na+ increased (P <.0001), whereas the concentration of K+ presented an initial elevation followed by hypokalemia (P = 0.0025). After induction, there was an increase in L-lactate (P = 0.0039) and LDH (P = 0.0005) and cTnI, CK-MB, CK, AST and GGT did not change (P> 0.05). Therefore, the evaluation of blood biochemistry aided in the monitoring of systemic changes resulting from ARLA in goats and the clinical condition induced by this experimental model did not cause cardiac injury.
Keywords: Acid-base balance; Blood gas; Cardiac troponin I; Creatine kinase MB; Electrolytes; Ruminal acidosis